Veterans in the criminal justice system (CJS) in England and Wales. (19th October 2011) - Bray, Isabelle; O'Malley, Paula
Abstract : Objectives: (1) Determine the proportion of those in prison or on probation who are veterans of the Regular Armed Forces; (2)describe the demographic characteristics and offence groups of veterans in prison or on probation; (3) compare the proportion of veterans in prison/on probation with the proportion of the general population in prison/on probation. Methods: This is a cross-sectional study based on matching administrative data. A database of Regular Service leavers was linked to a snapshot of all those in prison on 06/11/09 and a list of all those subject to a Community Order, Suspended Sentence or Post-release Supervision on 30/09/09. Results: Adjusting for the incompleteness of the Service leavers' database, we estimate that 3.5% of prisoners and 3.4% of those on probation in England and Wales are veterans. Half of the veterans in prison were ≥45 years and nearly all were men. The most common offence group for veterans in the CJS was 'violence against the person'. For men aged 18–54 years (and adjusting for differences in age structure of the two populations), the proportion of the general population in prison was 54% (95% CI 37% to 49%) higher than it was for veterans; the proportion of the general population on probation was 12% (95% CI 9% to 15%) higher than it was for veterans. Conclusions: We estimate there are 2820 Regular veterans in prison and 5860 on probation in England and Wales. These estimates contrast with figures released in 2009 by the National Association of Probation Officers of 8500 in prison and 12 000 on probation.